The Potential for Youth Programs to Promote African American Youth's Development of Ethnic and Racial Identity. (7th November 2016) - Brittian Loyd, Aerika; Williams, Brittney V.
Abstract: Effective programs for youth can reduce problem behaviors and promote positive development. In particular, cultural assets (e.g., ethnic–racial identity) are important for African American youth's health and development. In this article, we argue that youth programs represent an important social context for African American youth's development of positive ethnic–racial identity, and we present a conceptual framework for understanding how such programs may affect African American youth's development in this area. Then, we provide examples of evidence‐based programs that have assessed this developmental process among African American youth. We conclude with considerations for research.